Haze and air pollution : the potential health crisis - Gianna Gayle Amul (2014)
The link between environmental health and health security has always been understated. The lack of multi-sectoral mechanisms to address the health consequences of air pollution caused by forest fires can have detrimental effects on the region’s critical social infrastructure – its people.